1998
DOI: 10.1538/expanim.47.97
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Maternal Effects on Body Weight in Cross-fostering Experiment on Two Subspecies of Mice.

Abstract: A cross-fostering experiment was conducted on two quite distinct subspecies of mice, domesticated laboratory mouse of CF#1 (Mus musculus domesticus) and Yonakuni wild mouse (Yk, Mus musculus molossinus yonakuni), to estimate the prenatal and postnatal maternal effects on body weight of offspring. Mating was done between subspecies, two or three females being mated to a male at nine-ten weeks of age. Two dams of different subspecies that littered at the same day were used as a group of foster dams. Litters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A number of factors in the gestational environment have important effects on offspring development. Cross-fostering studies in mice suggest that the prenatal environment accounts for 61-96% of variance in body weight gain in male pups and 35-92% in female pups (42). Maternal undernutrition, high-fat diet feeding, and maternal stress during gestation can predispose offspring to obesity (42).…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors in the gestational environment have important effects on offspring development. Cross-fostering studies in mice suggest that the prenatal environment accounts for 61-96% of variance in body weight gain in male pups and 35-92% in female pups (42). Maternal undernutrition, high-fat diet feeding, and maternal stress during gestation can predispose offspring to obesity (42).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, maternal care was linked with changes in body weight and height of the pups divergently selected for these traits. Although the genotype influence prevailed [ 23 , 24 ], it was confirmed later on two distinct murine populations without any preselection considering weight or height criteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature on maternal effects and metabolic functioning in both humans and other animals (eg, sheep, rodents) is unequivocal. [7][8][9][10][11][12] Ovum transfer, animal breeding, and crossfostering studies have clearly documented that the intrauterine milieu and early postnatal periods can induce or ameliorate metabolic dysfunction in a single generation, independent of genotype. Recently, an embryo transfer study by Garg et al 13 found that the inheritance of pathologic metabolic phenotypes can be ameliorated when the embryo is transferred and gestated in a "normal metabolic environment."…”
Section: Accumulative and "Corrective" Maternal Effectsmentioning
confidence: 99%